Survey on international cooperation for development in Mexico and its current institutional framework - Pérez, Jorge; Ayala, Citlali (Papeles de Europa, 2016)
Facing the transition of the Millennium Development Goals towards the Sustainable Development Goals from 2016 onwards, and facing a more formal cooperation in Mexico with the creation of its Agency in 2011, it becomes relevant to know the current situation on the international cooperation in the country. Hence, the current paper, summarize the main outcomes of an opinion survey based on the point of view of leaders and experts on the subject, that was applied along 2014 over observed trends on challenges and implications for Mexico, either as a recipient, donor or dual country and for its foreign policy, but mainly for the participation and execution of the 2030 Agenda.
Keywords: International Cooperation; Development